Cardiorespiratory Responses During Progressive Upper- and Lower-Body Water exercise - AGISHI, Yukou; FUJISAWA, Hiroyuki; OHMICHI, Kenichi (Journal of exercise physiology, 1993)
Cardiorespiratory resposes of ten untrained subjects were evaluated during Upper and Lower-Body exercise while immersed to the neck in 38°C water. Upper-Body exercise was flexion and extension of elbow joint(EFE), and then Lower-body exercise was flexion and extension of knee joint(KFE). The Test was started at degree of 20 repititions/min and every 3 min increased by 10 repitions/min until reached to 60 repitions/min(stage I ?? V). Mean values of metabolic equivalents (1 METS = 3.5ml/kg/min) increased 1.4 to 4.1 for EFE, from 1.1 to 4.0 for KFE. Relationship of Heart Rate and Oxgen Consumption was similar for EFE and KFE.